An evaluation of the FDA's analysis of the costs and benefits of the graphic warning label regulation. Issue 2 (30th December 2014) - Chaloupka, Frank J; Warner, Kenneth E; Acemoğlu, Daron; Gruber, Jonathan; Laux, Fritz; Max, Wendy; Newhouse, Joseph; Schelling, Thomas; Sindelar, Jody
Abstract : The Family Smoking Prevention and Tobacco Control Act of 2009 gave the Food and Drug Administration (FDA) regulatory authority over cigarettes and smokeless tobacco products and authorised it to assert jurisdiction over other tobacco products. As with other Federal agencies, FDA is required to assess the costs and benefits of its significant regulatory actions. To date, FDA has issued economic impact analyses of one proposed and one final rule requiring graphic warning labels (GWLs) on cigarette packaging and, most recently, of a proposed rule that would assert FDA's authority over tobacco products other than cigarettes and smokeless tobacco. Given the controversy over the FDA's approach to assessing net economic benefits in its proposed and final rules on GWLs and the importance of having economic impact analyses prepared in accordance with sound economic analysis, a group of prominent economists met in early 2014 to review that approach and, where indicated, to offer suggestions for an improved analysis. We concluded that the analysis of the impact of GWLs on smoking substantially underestimated the benefits and overestimated the costs, leading the FDA to substantially underestimate the net benefits of the GWLs. We hope that the FDA will find our evaluation useful in subsequent analyses, not only of GWLs but also of other regulations regarding tobacco products. Most of what we discuss applies to all instances of evaluating the costs and benefits of tobacco product regulation and, we believe, should be considered in FDA's future analyses of proposed rules.